2021
DOI: 10.1007/s00204-021-03127-8
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent tagging of endogenous Heme oxygenase-1 in human induced pluripotent stem cells for high content imaging of oxidative stress in various differentiated lineages

Abstract: Tagging of endogenous stress response genes can provide valuable in vitro models for chemical safety assessment. Here, we present the generation and application of a fluorescent human induced pluripotent stem cell (hiPSC) reporter line for Heme oxygenase-1 (HMOX1), which is considered a sensitive and reliable biomarker for the oxidative stress response. CRISPR/Cas9 technology was used to insert an enhanced green fluorescent protein (eGFP) at the C-terminal end of the endogenous HMOX1 gene. Individual clones we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 93 publications
0
16
0
Order By: Relevance
“…Oxidative stress can accelerate the process of IDD in many ways, including through apoptosis, ECM degeneration, senescence, and autophagy (Feng et al, 2017). Many reports have shown that BARD has a strong antioxidative effect (Khurana et al, 2020;Pang et al, 2021;Snijders et al, 2021). However, whether BARD can alleviate IVD degeneration caused by compression has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress can accelerate the process of IDD in many ways, including through apoptosis, ECM degeneration, senescence, and autophagy (Feng et al, 2017). Many reports have shown that BARD has a strong antioxidative effect (Khurana et al, 2020;Pang et al, 2021;Snijders et al, 2021). However, whether BARD can alleviate IVD degeneration caused by compression has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…We used the human iPSC lines mciPS (model no. SC301A-1; System Biosciences, Palo Alto, CA, USA), SBAD2 [75], Sigma iPSC0028 (Si28) (EPITHELIAL-1, #IPSC0028, Merck, Darmstadt, Germany) and the transgenic iPSC line Si28-NGN1. IPSC cultures were maintained under xeno-free conditions (see supplementary methods) [76].…”
Section: Methodsmentioning
confidence: 99%
“…As hPSCs are highly proliferative, editing their genome is more readily feasible compared to primary human liver cells that have limited expansion capacity. Therefore, they are amenable to the creation of fluorescent stress pathway reporters [26][27][28][48][49][50][51]. These reporters can be generated by introducing an exogenous promoter and reporter gene in 'safe harbor' loci, such as the adeno-associated virus integration site 1 (AAVS1) locus [28,52], the citrate lyase beta-like gene locus (CLYBL) [53] or the ROSA26 locus [54] in iPSCs.…”
Section: Ipsc Reporter Linesmentioning
confidence: 99%
“…This allows monitoring of not only the presence of a specific protein but also the sub-cellular localization of the protein of interest. As an alternative for the linker sequence, an internal ribosomal entry site (IRES) or a 2A peptide sequence can be used, which will lead to the translation of two separate proteins [48,49,51,56]. These fluorescent reporter lines allow for the monitoring of cellular pathways, studying the mode of action (MOA) of drug toxicity or to investigate in vivo transplanted PSC-derived progeny [26].…”
Section: Ipsc Reporter Linesmentioning
confidence: 99%
See 1 more Smart Citation